2020
DOI: 10.3390/w12020373
|View full text |Cite
|
Sign up to set email alerts
|

Water Use Efficiency of Soybean under Water Stress in Different Eroded Soils

Abstract: Soil erosion could change the effective storage of soil moisture and affected crop water use efficiency (WUE). To quantitative study differences in the WUE of soybean and the crop’s response to water stress for soils with different degrees of erosion in northeastern China, three erosion degrees—(1) lightly, (2) moderately and (3) severely—eroded black undisturbed soils and four years (from 2013 to 2016) of soybean pot experiments were used to control soil water content (100%, 80%, 60%, and 40% field capacity (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 73 publications
1
3
0
Order By: Relevance
“…Thus, nutrient transport to plant tissue will also be lower. This is in line with research conducted by Li et al (2020) that soybean plants grown in plastic houses with reduced water supply intervals caused a decrease in plant height by 9.2%. In addition, research conducted by Kumar, Rao, Mohanty, Selvi, & Bhoi (2015) shows that soybeans that are given drought stress by reducing the intensity of water supply in the generative phase also cause a reduction in plant height.…”
Section: Resultssupporting
confidence: 92%
“…Thus, nutrient transport to plant tissue will also be lower. This is in line with research conducted by Li et al (2020) that soybean plants grown in plastic houses with reduced water supply intervals caused a decrease in plant height by 9.2%. In addition, research conducted by Kumar, Rao, Mohanty, Selvi, & Bhoi (2015) shows that soybeans that are given drought stress by reducing the intensity of water supply in the generative phase also cause a reduction in plant height.…”
Section: Resultssupporting
confidence: 92%
“…However, plants can tolerate water stress only up to a certain limit (threshold level) and beyond that limit, there is a severe decline in yield [ 6 ]. In soybean case, it was reported that at 40% field capacity, plants experience severe drought stress [ 7 ]. It exists due to low moisture in the soil at a certain time, therefore the available water for plants is limited [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…to fix 1 μmol CO 2 , 0.175 mmol H 2 O must be used (or to fix 1 g CO 2 , 72 g H 2 O must be used). However, it should be noted that WUEi values are highly variable during the day and growth stage and depend on genotypic features (Lopez et al 2019, Li et al 2020. However, in our experiments, measurements were carried out under controlled conditions, and changes in the A n and T r rates were obtained due to the direct action and after-effect of water stress at different stages of plant development, as well as seeds inoculation by rhizobia with various NMC.…”
Section: Original Papermentioning
confidence: 97%